DINAMIKA PENDIDIKAN ISLAM DI INDONESIA ERA PEMERINTAHAN KOLONIALISME JEPANG - Siti Aminah Lubis; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
This research aims to investigate the political dynamics of Islamic education during the period of Japanese colonialism, specifically focusing on its influence on Islamic educational institutions, curricula, and the religious identity of local communities. Through a qualitative approach involving historical analysis and document analysis, this research reveals how the Japanese colonial government manipulated Islamic education as a tool to achieve its political goals, including strengthening colonial domination and controlling public opinion. Apart from that, this research also explores the response and resistance of the local Muslim community to the educational politics imported by the Japanese colonial government. The results of this research provide in-depth insight into the complexity of the relationship between colonial power, religious education, and religious identity in the historical context of Islamic education under Japanese colonialism. It is hoped that the implications of these findings will contribute to a better understanding of the political dynamics of Islamic education and the interactions between colonial powers and local communities in specific historical contexts.